Pengaruh Supervisi Kepala Sekolah Dan Kompetensi Guru Terhadap Kinerja Guru Di Sekolah Dasar Negeri Se-Kecamatan Bula - Fidmatan, Firdah; Kempa, R.; Sahalessy, A.; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to (1) Describe the supervision of school principals in State Elementary Schools in Bula District. (2) Describe the competency of teachers in State Elementary Schools in Bula District. (3) Describe the performance of teachers in State Elementary Schools in Bula District. (4) Describe whether or not there is a significant influence between principal supervision on teacher performance in State Elementary Schools in Bula District. (5) Describe whether there is a significant influence between teacher competency on teacher performance in State Elementary Schools in Bula District. (6) Describe whether or not there is a significant influence between principal supervision and teacher competency together on teacher performance in State Elementary Schools in Bula District. This type of research is quantitative research. The samples obtained came from state elementary schools in Bula District, East Seram Regency. The sample used was 106 respondents. The data obtained in this research was through filling out a questionnaire. The research method used by researchers in this research is descriptive quantitative with quantitative regression analysis methods. The results of descriptive analysis of principal supervision variables in Bula District Elementary Schools, East Seram Regency are classified as moderate, Teacher Competency variables in Bula District East Seram District Elementary Schools are classified as high, and teacher performance variables in Bula District Elementary Schools are classified as high, and teacher performance variables in Bula District Public Elementary Schools Eastern Seram Regency is relatively high. The results of the descriptive analysis based on the results of testing the first hypothesis show that the principal's supervision has a significant influence on teacher performance. The second hypothesis also shows that teacher competence has a significant influence on teacher performance. The third hypothesis shows that principal supervision and teacher competence together have a significant influence on teacher performance in State Elementary Schools in Bula District, East Seram Regency.